In-situ immobilization of selected heavy metals using different source of phosphate amendments for organic production of misai kucing (Orthosiphon stamineus Benth) - Mulana@Maulana, Khairun Naim (2017)
Sustainable organic herbal production requires utilization of bio-waste materials as plant nutrient sources due to its economical aspect and would ensure continuous productivity. The usage of organic wastes in organic farming system (OFS) as fertilizers and soil amendments should be monitored as the accumulation of heavy metals has been reported in several studies. This study was set up to investigate the effect of chicken manure soil application on heavy metals concentration in organically grown O. stamineus and a potential approach to immobilize it using phosphate based amendments. Glasshouse trials has been conducted for study 1 and study 3 whilst incubation study was conducted for study 2 accordingly. Results in the study 1 indicated that the trace metals of lead (Pb) and Zn (Zn) exceeds the threshold value allowed by Pharmacopeia in herbs and by Malaysian Food Act (1983) and Food Regulations (1985) at 10 and 40 mg/kg respectively. This is postulated due to application of chicken manure and organic materials during cultivation. In study 2, 2 sources of apatite were tested: - 1) Egyptian rock phosphate (ERP) and 2) bone meal (BM) under incubation study. The results demonstrated that the dominant lead forms were mainly associated with residual, carbonates and also exist in exchangeable form. From this study, the suitable rate for reducing phyto-available lead in the soil system applied with 10 t/ha chicken manure is at 1 t/ha of Egyptian rock phosphate and 2 t/ha of bone meal. In the third study, the effectiveness of phosphorus on reducing heavy metals were evaluated under controlled condition in the glasshouse. Results demonstrated heavy metals accumulated in the aerial parts of O. stamineus with copper (18.3-37.7 mg/kg), zinc (60.9-92.0 mg/kg) and lead (1.9-3.6 mg/kg). From the fractionation study, the percentage of exchangeable fraction was reduced with application of P-amendments with the highest of 20.2% reduction recorded for 2 t/ha application of triple super phosphate. This is followed by reduction in exchangeable fraction for others treatments: 2 t/ha of bone meal (4.1%), 4 t/ha of bone meal (5.1%), 1 t/ha of Egyptian rock phosphate (8.1%) and 2 t/ha of Egyptian rock phosphate at 17.6%. Applications of P-amendments tested shows effectiveness of TSP in reducing lead in soils. The best treatments are as follows: - 2 t/ha of triple super phosphate> 2 t/ha of Egyptian phosphate rock> 1 t/ha of Egyptian rock phosphate> 4 t/ha of bone meal> 2 t/ha of bone meal. These treatments were recorded as being able to stabilize the Pb as indicated in the percentage reduction of phytoavailable pools into a more stable form of residual pool.